2016
DOI: 10.1080/13651501.2016.1249892
|View full text |Cite
|
Sign up to set email alerts
|

Postural changes in different stages of schizophrenia is associated with inflammation and pain: a cross-sectional observational study

Abstract: CRP was associated with disease severity, while vWF and pain were associated with forward head posture, hyperlordosis and scoliosis, suggesting an association between vascular inflammation and pain, with an influence on posture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…Our theory-independent MM are in line with results of the few previous studies analyzing posture and gait disturbances in people with schizophrenia [ 39 41 , 48 , 68 , 69 ]: Cristiano et al [ 69 ] identified forward head tilt as the most common postural feature in early and late-stage schizophrenia and found associations of postural changes with disease severity. Similarly, we identified the head posture as only significant posture marker and found associations of an increased “hanging” of the head with higher levels of NSS items “Station and Gait”, “Tandem Walk” and NSS subscales “Motor Coordination” and “Sensory Integration”.…”
Section: Discussionsupporting
confidence: 91%
“…Our theory-independent MM are in line with results of the few previous studies analyzing posture and gait disturbances in people with schizophrenia [ 39 41 , 48 , 68 , 69 ]: Cristiano et al [ 69 ] identified forward head tilt as the most common postural feature in early and late-stage schizophrenia and found associations of postural changes with disease severity. Similarly, we identified the head posture as only significant posture marker and found associations of an increased “hanging” of the head with higher levels of NSS items “Station and Gait”, “Tandem Walk” and NSS subscales “Motor Coordination” and “Sensory Integration”.…”
Section: Discussionsupporting
confidence: 91%
“…It is still not clear when these deficits emerge, but it has been suggested that they could arise in the earlier stages of disease [17,18]. Indeed, postural changes were found when comparing early-vs late-stage schizophrenia, with-surprisingly-a higher degree of severity in the earlier disease stages [18]. All together, these findings strongly propose the motor dimension as a strong endophenotypic candidate for schizophrenia [5].…”
Section: Introductionmentioning
confidence: 99%
“…However, previous research on different psychiatric conditions, including schizophrenia, described some recurrent features like slower gait, shorter stride length and balance problems in these individuals [16]. It is still not clear when these deficits emerge, but it has been suggested that they could arise in the earlier stages of disease [17,18]. Indeed, postural changes were found when comparing early-vs late-stage schizophrenia, with-surprisingly-a higher degree of severity in the earlier disease stages [18].…”
Section: Introductionmentioning
confidence: 99%
“…There is extensive evidence of endothelial dysfunction and inflammation in many patients with SZ which includes high levels of sICAM-1, sVCAM1 and vWF in the periphery and high levels of VCAM-1, VE-cadherin and a range of tight junction proteins in the brain [411][412][413][414][415]. However, there is increasing evidence that endothelial activation and dysfunction may be confined to or at least be greatly enhanced in an inflammatory subtype of schizophrenia [411,415].…”
Section: Interdependency Of Endothelial Dysfunction and Inflammationmentioning
confidence: 99%